UPAYA HUKUM PASCAPUTUSAN PRAPERADILAN DALAM RANGKA MENEGAKKAN HUKUM DAN KEADILAN - Faisal Abdaud (Institut Agama Islam Negeri (IAIN) Kendari, 2018)
In the current legal development there are several cases of pretrial decisions which are then not followed up by law enforcement while other pretrial judgments are in fact reciprocated with extraordinary resistance.The method used in this study is empirical normative research, which normatively / juridically examines the rules of legislation related to post-pretrial legal action.The result of the research is The validity of the suspect's appointment may be requested by the investigator or suspect or his family or his proxy for a maximum of 7 days must be decided as a provision which is ideal in bringing the birth of KUHAP into a new face.